A Medeia do subúrbio : escrita contemporânea e desamparo freudiano em Álbum de família de Nelson Rodrigues - Tavares, José Luiz Cordeiro Dias (2022)
The urgency of political, social, and intellectual transformations in the post-war period resulted in the transgression of previously established boundaries. The limits of social conventions were blurred, allowing for the fertile expansion of borders, including those between fiction and nonfiction. From here onwards, we set out to characterize contemporary writing as our first line of interest, in which different categories, such as self-fiction, metafiction, autobiography or even other languages such as photographic material, may be used. In contemporary writing, nothing is exactly new, but rather a new way of literary construction in which both the content and the way in which the work is narrated are important. It is not uncommon for literary, or even theatrical critics to attribute to Nelson Rodrigues a central role in the renewal of Brazilian dramaturgy in the 1940s. The choice for this author and, in particular, of Álbum de família as the corpus of this study, was made when we asked ourselves about the possibility of facing an example of contemporary writing. This is, therefore, the first interrogation of this work and is based on the hypothesis that we find in this work the literary elements that reveal the features of self-fiction and hybridity of languages as strategies used by Nelson to prepare the writing of this work. The second interrogation is related to the hypothesis that the aesthetic resource that best expresses Nelson's subjectivity in Álbum de família is the helplessness in the Freudian sense of the concept [Hilflosigkeit]. As a prisoner of his peculiar perspective in which his own obsessions howl, Nelson tells us of the helplessness that structures the framework of that family. It is in this state that the affliction of all the characters is woven, especially Senhorinha in her marriage to Jonas. In her suffering, Senhorinha gets close to Medeia, an icon of the helplessness experienced in her marriage to Jasão. Medeia kills her children and takes them out of life. Senhorinha takes the lives of her children and withdraws herself from the scene. Both did not elaborate their afflictions and find themselves exiled from their affective continents. For this reason, Medeia was invited to dialogue with Senhorinha in this work. To explore the understanding of Greek tragedy and modern drama, we turned mainly to Aristotle, Peter Szondi and Anatol Rosenfeld. For our reflections on the work of literary writing itself and its authors, we looked for references in Antonio Candido, Alfredo Bosi, Décio de Almeida Prado, Umberto Eco, Jean Paul Sartre, Roland Barthes and Michel Foucault, among others. To elaborate our propositions about contemporary writing, we essentially made use of the perspectives by Ana Paula Arnaut, Linda Hutcheon and Leyla Perrone Moisés in addition to Philippe Lejeune and Serge Doubrovsky. In the chapters that psychoanalysis was addressed and, in particular, for the issue of helplessness, we mainly resorted to the postulates of Sigmund Freud in addition to some contributions by Ferdinand de Saussure and Jacques Lacan. We developed our reflections alongside them. They helped us formulate the propositions that support the aspects presented here for the reading of this corpus, namely, contemporary writing and helplessness [Hilflosigkeit]. The objective is that the literary and aesthetic resources explored here will provide something new to the critical fortune of Álbum de família, which usually dedicates its gaze to tragedy and incest and which we seek to expand by means of our work